Challenges to Evaluating Physical Activity Programs in American Indian/Alaska Native Communities. (June 2018) - Roberts, Erica Blue; Butler, James; Green, Kerry M.
Despite the importance of evaluation to successful programming, a lack of physical activity program (PAP) evaluation for American Indian/Alaska Native (AI/AN) programs exists, which is significant given the high rates of obesity and diabetes in this population. While evaluation barriers have been identified broadly among AI/AN programs, challenges specific to physical activity (PA) programming are unexplored. To address this gap, a research study was conducted involving 17 in-depth interviews with evaluation staff of externally funded AI/AN PAPs. A thematic analysis revealed factors hindering meaningful program evaluation: cultural characteristics that challenge traditional evaluation, the logistics of PA programming, measurement and data collection challenges, lack of resources and support, and lack of alignment between funding agency requirements and the evaluation desired by AI/AN organizations. Some challenges are general to PAPs and others specific to AI/AN organizations. Findings identify ways to improve culturally responsive evaluation for AI/AN PAPs.